Анализ микроструктуры циркониевых сплавов с использованием компьютерных методов - Чубарова, Я. А.; Гордая, А. П. (НТУ "ХПИ", 2004)
In the given article are presented results of metallography researches of the cladding tubes of Ukrainian (Zrl%Nb) and Russian (E-110) make. The computer program uses for processing images of the materials microstructure, offered for use in estimation of the quality according to the grain size and amount of second phase per a section unit
Keywords: ядерная энергетика; тепловые нейтроны; твэл; излучения; оболочки твэл